2006
DOI: 10.1111/j.1399-0012.2006.00523.x
|View full text |Cite
|
Sign up to set email alerts
|

Creatinine‐based formulae for the estimation of glomerular filtration rate in heart transplant recipients

Abstract: Chronic renal failure (CRF) is a common complication in heart transplant patients. Serum creatinine has clear limitations for the detection and estimation of glomerular filtration rate (GFR). Various creatinine-based formulae are classically used for GFR estimation, but little scientific evidence exists for such use in a heart transplant population. GFR was measured using the plasmatic clearance of the glomerular tracer (51)Cr-EDTA in 27 heart transplant patients with two measures for 22 of the patients. Forty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 56 publications
3
14
1
1
Order By: Relevance
“…This is partly explained by the fact that equations based on creatinine considerably overestimate GFR in renal transplantation (154)(155)(156). Overall, equations using CysC appear to offer better predictive performance, although it remains to be shown that this improvement in prediction is clinically significant (52, 131, 133, 157, 158).…”
Section: Utility Of Cysc In Transplantationmentioning
confidence: 89%
“…This is partly explained by the fact that equations based on creatinine considerably overestimate GFR in renal transplantation (154)(155)(156). Overall, equations using CysC appear to offer better predictive performance, although it remains to be shown that this improvement in prediction is clinically significant (52, 131, 133, 157, 158).…”
Section: Utility Of Cysc In Transplantationmentioning
confidence: 89%
“…9 Recent studies suggest that the formulas are similarly limited in estimating kidney function in lung and heart recipients as well. 12,13 The largest and most comprehensive study of CKD prevalence after solid-organ transplantation used a definition of GFR of Ͻ30 ml/min per 1.73 m 2 body surface area, calculated with the fourvariable MDRD equation. Applying this definition to a data set from the Scientific Registry of Transplant Recipients (SRTR), Ojo et al 1 reported a CKD prevalence at 5 yr after transplantation of 21.3% among intestine recipients, 18.1% among liver recipients, 15.8% among lung recipients, 10.9% among heart recipients, and 6.9% among heart-lung recipients.…”
Section: Prevalence Of Ckd After Nonrenal Organ Transplantationmentioning
confidence: 99%
“…Limits of agreement (ME ± 2 SD) were only provided in 12 studies [13,16,23,26,27,28,29,30,31,32,33,34]. In articles that did not provide them, the SD of the ME and of the MPE were extracted from the distance between the limits of agreement of the Bland-Altman plot [26,27,28,29]. …”
mentioning
confidence: 99%